Management of an upstream barrio school a case study - Guarino, Adela G. (2006)
This case study aimed to identify the varied roles and functions performed by the principal as manager of upstream barrio elementary schools in Eastern Samar. The fieldwork for this ethnographic study took six months and involved participant observation, interviews of the principal/district supervisor, teachers, parents, barangay officials, and visits to the different upstream barrios. The pricipal/district supervisor manages upstream barrio schools through professional autonomy. In view of the conclusions of this case study, a paradigm of management by proxy emerges with the roles of the principal/district supervisor as a vision provider, teacher of teachers, motivator of professionals, expert communicator, human relations officer, and a builder of collaborative schools.